1993
DOI: 10.1111/j.1464-410x.1993.tb16057.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Renal Blood Flow, Glomerular Filtration Rate or 99mTc‐DMSA Uptake Predict Outcome in Experimental Unilateral Renal Obstruction?

Abstract: Single kidney glomerular filtration rate (SK GFR), single kidney blood flow (SK BF) and differential renal function (DRF), using both technetium labelled diethylene-pentaacetic acid (99mTc-DTPA) and dimercaptosuccinic acid (99mTc-DMSA), were examined as predictors of outcome in a pig model of complete unilateral ureteric obstruction. SK GFR and SK BF were unable to predict outcome following relief of obstruction but there was a high curvilinear correlation between DRF assessed at the end of defined periods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, it is well known that a radiological technician computes DRF and the value is subject to variability, depending on where the outlined regions of interest are drawn. [13][14][15] Apart from radionuclide assessment, some biochemical markers in the urine have been proposed to help determine whether a hydronephrotic kidney requires surgery or can be safely monitored without fear of parenchymal damage. Various biochemical indicators of the response of the kidney to obstructive damage have been investigated, and some of them have clinical promise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is well known that a radiological technician computes DRF and the value is subject to variability, depending on where the outlined regions of interest are drawn. [13][14][15] Apart from radionuclide assessment, some biochemical markers in the urine have been proposed to help determine whether a hydronephrotic kidney requires surgery or can be safely monitored without fear of parenchymal damage. Various biochemical indicators of the response of the kidney to obstructive damage have been investigated, and some of them have clinical promise.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 However, it is well known that differential functional renal (DRF) activity computed by a radiology technician and its value is subject to extreme variability, depending on where the evaluated regions of interest are drawn. [12][13][14][15] Levels of biochemical markers, such as certain enzymes and microproteins, in urine obtained from obstructed renal units may have a role in predicting the final outcome of corrective surgery in patients with apparent uretero-pelvic obstruction. However, studies have shown that the biochemical markers have limited application and reliability because of extremely variable results.…”
Section: Introductionmentioning
confidence: 99%